2001
DOI: 10.1124/mol.60.5.1091
|View full text |Cite
|
Sign up to set email alerts
|

Mercapturic Acids (N-AcetylcysteineS-Conjugates) as Endogenous Substrates for the Renal Organic Anion Transporter-1

Abstract: Mercapturic acids are N-acetyl-L-cysteine S-conjugates that are formed from a range of endogenous and exogenous chemicals. Although the kidney is a major site for elimination of mercapturic acids, the transport mechanisms involved have not been identified. The present study examined whether mercapturic acids are substrates for the renal basolateral organic anion transporter-1 (Oat1) from rat kidney. This carrier mediates uptake of organic anions from the bloodstream in exchange for intracellular ␣-ketoglutarat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…11B). The fact that DMPS is a substrate for OAT1 is further underlined by the recent findings of Pombrio et al (Pombrio et al, 2001). They concluded that selected mercapturic acids serve as high affinity substrates for OAT1.…”
Section: Discussionmentioning
confidence: 87%
“…11B). The fact that DMPS is a substrate for OAT1 is further underlined by the recent findings of Pombrio et al (Pombrio et al, 2001). They concluded that selected mercapturic acids serve as high affinity substrates for OAT1.…”
Section: Discussionmentioning
confidence: 87%
“…In fact, mercapturic acids have been shown previously to be secreted by the renal proximal tubule (Stevens and Jones, 1989). In addition, it was recently shown that several mercapturic acids [i.e., S-(2,4-dinitrophenyl)-N-cysteine] are specific hOAT1 substrates (Pombrio et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The animals were anesthetized with 0.3% tricaine (Sigma), decapitated, pithed, and the ovaries were removed. Stage V and VI oocytes were isolated by collagenase digestion as previously described (6,13,26). All animal procedures were carried out in accord with protocols approved by the NIEHS Animal Care and Use Committee.…”
Section: Animalsmentioning
confidence: 99%